2019
DOI: 10.1002/lno.11309
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical basis for the loss of bioluminescence in the dinoflagellateNoctiluca scintillansalong the west coast of the U.S.A.

Abstract: The globally distributed heterotrophic dinoflagellate Noctiluca scintillans (Macartney) Kofoid & Swezy is well known for its dense blooms and prominent displays of bioluminescence. Intriguingly, along the west coast of the U.S.A., its blooms are not bioluminescent. We investigated the basis for this regional loss of bioluminescence using molecular, cellular, and biochemical analyses of isolates from different geographic regions. Several prominent differences were identified in the nonbioluminescent strains: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 112 publications
(165 reference statements)
0
7
0
1
Order By: Relevance
“…In these organisms, bioluminescence is sensed by mechanical stimuli which account for the light rising from waves braking on shoreline or from wakes of ships, and have also inspired the development of biotechnological strategies, such as polymersomes nanoreactors activable by shear stress to control biocatalytic reactions [241,242]. On the other hand, Dinoflagellates are a preferred model to investigate the still greatly unrevealed biological meaning of bioluminescence of these microorganisms, for example with attention to elucidate both evolution and ecological effect of non-luminescent or toxic populations [243][244][245].…”
Section: Bioluminescencementioning
confidence: 99%
“…In these organisms, bioluminescence is sensed by mechanical stimuli which account for the light rising from waves braking on shoreline or from wakes of ships, and have also inspired the development of biotechnological strategies, such as polymersomes nanoreactors activable by shear stress to control biocatalytic reactions [241,242]. On the other hand, Dinoflagellates are a preferred model to investigate the still greatly unrevealed biological meaning of bioluminescence of these microorganisms, for example with attention to elucidate both evolution and ecological effect of non-luminescent or toxic populations [243][244][245].…”
Section: Bioluminescencementioning
confidence: 99%
“…Thus, N. scintillans often causes a red ocean during the day and a glowing ocean at night. There have been many studies on the red tides and bioluminescence of N. scintillans (Sweeney 1971, Tett 1971, Uhlig and Sahling 1990, Buskey 1995, Valiadi and Iglesias-Rodriguez 2014, Valiadi et al 2019. Red-tide patches containing N. scintillans provide a large-scale bright bioluminescence field when bioluminescent cells in the patches are hit by waves, swimming fish and mammals, moving boats, ships, and submarines (Tarasov 1956, Bityukov 1971, Hastings 1975, Morin 1983, Williams and Kooyman 1985, Rhor et al 1998.…”
Section: Design Of An Automatic System Of Cultivating Noctiluca Scint...mentioning
confidence: 99%
“…While several experimental studies support some of these hypotheses [ 75 , 333 , 336 ] some characteristics of dinoflagellate bioluminescence may suggest that it could also have other functions. For example, some strains of Noctiluca scintillans off the west coast of the USA have lost their bioluminescence but are still able to form dense populations despite the presence of predators, thus questioning the ecological role of bioluminescence in this species [ 337 ]. Moreover, some studies have reported that many species of dinoflagellates can spontaneously emit light flashes, without being mechanically stimulated [ 334 , 338 , 339 ].…”
Section: Hypothesis: Bioluminescence Signalling In the Unicellular Worldmentioning
confidence: 99%